Independent creative village program as an effort to prosper the community based on village potential - Adi Nugraha; Yudhistira Saputra (Journal of Community Service in Science and Engineering (JoCSE), 2023)
An independent village is a village that can carry out village development to improve the quality of life and life as much as possible for the welfare of rural communities with social resilience, economic resilience, and ecological resilience in a sustainable manner. One of the superior villages with a target to become an independent village is Panancangan Village, with various dynamic efforts to make it happen. Panancangan Village is one of the villages in Cibadak District, Lebak Regency, Banten Province. Three methods are used in the Independent Creative Village Program activities: internal discussions and online and offline activities. The independent creative village program has been implemented in this service activity. The activities include digital marketing seminars for MSMEs, health seminars (pulmonary TB), and traditional game competitions in the Republic of Indonesia's Independence Day framework. Desa mandiri adalah desa yang mempunyai kemampuan dalam melaksanakan pembangunan desa untuk meningkatkan mutu kehidupan dan kehidupan yang sebesar-besarnya demi kesejahteraan masyarakat pedesaan dengan ketahanan sosial, ketahanan ekonomi, dan ketahanan ekologi secara berkelanjutan. Salah satu desa yang unggul dan mempunyai target untuk menjadi desa mandiri adalah Desa Panancangan, dengan berbagai upaya dinamis yang dilakukan untuk mewujudkannya. Desa Panancangan merupakan salah satu desa yang berada di Kecamatan Cibadak, Kabupaten Lebak, Provinsi Banten. Metode yang digunakan dalam kegiatan Program Desa Kreatif Mandiri ini ada tiga metode, yaitu diskusi internal, aktivitas online dan aktivititas offline. Program desa kreatif mandiri telah diterapkan dalam kegiatan pengabdian ini. Kegiatannya berupa seminar digital marketing untuk UMKM, seminar kesehatan (TB Paru), lomba permainan tradisional dalam rangka Hari Kemerdekaan Republik Indonesia.